State University with Legal Entity and the Impact to the Rights and Obligations of the Tax Transaction: Case of the University of Indonesia - Nur, T F; Widodo, A; Mutiara, R (KnE Social Sciences, 2018)
Consider the dynamics of legal status of the University of Indonesia, the Government issued Law No. 12/2012 on Higher Education that is also the legal status of six (6) other universities. Universities have the autonomy to manage the higher education through the three pillars of high education (Tridharma Perguruan Tinggi) in accordance with the background, the objectives, as well as the ability of the university. The autonomy of the university carried out based on the principles of accountability, transparency, non-profit, quality assurance and the effectiveness and efficiency of academic and non-academic activity. University of Indonesia was given full autonomy to manage the universities including the source of financing that consists of government budget and public funds. The Agency of taxation is the taxpayer who is determined to carry out tax obligations. As a non-profit organization with legal entity, UI must legally state back the status as a subject of corporate taxes which have the impact of tax aspect. As the applied research, data obtained from literature studies and field data collection in the form of an interview to the Central Administration of the University and the tax office where the University of Indonesia in Depok is registered. Keywords: State University with the legal Entity, tax right and obligation, non-profit organization